Pengaruh Keteladanan Pembina Terhadap Pembentukan Karakter Santri Putra Asrama Hidayatul Qur’an Pondok Pesantren Darul Ulum Jombang - Akmal Cahya Ramadhan; Dhikrul Hakim; Agus Mahfudin (Sujud: Jurnal Agama, Sosial dan Budaya, 2025)
This study analyzes the influence of the mentor's exemplary behavior on the character formation of male students at the Hidayatul Qur'an Dormitory of Darul Ulum Islamic Boarding School, Jombang. The purpose of this study is to determine how much influence the mentor's exemplary behavior has on the character formation of students, including the importance of character for students' lives and the influence of mentor's exemplary behavior. Using a random sampling technique method of 10% of the total population, 85 students were obtained from a population of 555 male students, data were collected through documentation, observation and Likert scale questionnaires. Data analysis was carried out using percentages and simple linear regression. The results show that the influence of the mentor's exemplary behavior is classified as "GOOD" (77.29%) and the character formation of students is classified as "GOOD" (81%). For the results of simple linear regression in the table, the significance value (p) is 0.000 which is smaller than the significance level of 0.05. Thus, HO is rejected and Ha is accepted, indicating that the mentor's exemplary behavior significantly contributes to the character development of male students at the Hidayatul Qur'an Dormitory at the Darul Ulum Islamic Boarding School in Jombang.